A Terra e o arquétipo feminino: o lugar do paraíso em Antes de nascer o mundo, de Mia Couto - Paiva, Juliana Vittorazze Schroden de (2019)
This study analyses the presence of the myth of Promised Land and the feminine arquetype in Mia Couto’s book Antes de nascer o mundo from the perspective of Imaginary studies. Based on theoretical studies such as those of Gaston Bachelard, Gilbert Durand, Mircea Eliade and Joseph Campbell, we examine the symbolic elements of the man’s relation with the Earth, women and the society in the composition of the myth of the hero and the paradise. Similarly, we investigate in Couto’s book how the armed conflict in Moçambique impacts on the writer’s mythic writing on exile and forgetfulness/oblivion. We also include in this approach the dialectic relations between the regimes listed by Gilber Durand, such as diurnal and nocturnal, and its representation of the feminine, the masculine, the earth and the water, and to what extend these elements symbolize the ruptures and convergences, dramas and reconciliation of individuals.